When we all fall asleep, where do we go? [compact disc] - Eilish, Billie, 2001- (Darkroom/Interscope Records, 2019)
Rising pop star Billie Eilish follows up the successful release of her 2017 EP with her first full length album. It includes the singles when the party's over; you should see me in a crown; and bury a friend.